The relationship between dimensions of technical knowledge of young alpine skiing competitors and competitive performance - Puhalj, S.; Lešnik, B. (Annales Kinesiologiae, 2018)
In the research, the relationship between individual variables of technical assessment of free and competitive style alpine skiing and the criterion variable (competitive performance) are addressed. The criterion variable is the total number of points that was achieved in the Rauch Ski Cup in the season 2013/2014. Twenty selected alpine skiers between the ages of 12 and 14 were included in the research. Technical knowledge and tactics of alpine skiing were assessed in the free skiing (TFS) during two giant slalom races for the Rauch Ski Cup (TCS). In order to determine bivariate correlations between the TFS and TFC variables and the competitive performance, the Pearson correlation coefficient method was used. For this particular section of the study, it was confirmed that all the variables used were significantly related to the criterion variable. In the successive test, using the calculation of multiple regression coefficients, we confirmed the high percentage of the explained variance of the two sets of measurements (TFS and TCS). In this research, the influence of technical knowledge of skiing in the free (TFS) and competitive skiing (TCS) on the competitive performance of alpine skiing in Slovenia was studied for the first time. Based on the results of the research, the foundation for both an improved concept of psychophysical and technical training and for the modernization of the selection criteria for the young competitors in alpine skiing will be proposed.